2007
DOI: 10.1002/jmv.20963
|View full text |Cite
|
Sign up to set email alerts
|

HBsAg non-reactive HBV infection in blood donors: Transmission and pathogenicity

Abstract: Five blood donors with occult persistent and one donor with an early window phase HBV infection were identified. They were negative in regular HBsAg screening and had low levels of HBV DNA that were probably not detectable by current mini-pool nucleic acid amplification testing. In four donors several mutations were found located in the HBs antigen loop. In three donors the mutations were predominantly outside the ''a'' determinant; one donor had a wild type HBsAg sequence. Fifty-five recipients of donations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(100 citation statements)
references
References 15 publications
4
95
0
Order By: Relevance
“…He developed typical acute hepatitis B five months later [12] . A second similar case has also been described [13] . The long early window period leads to the relatively large residual risk of 1: 360,000 for undetected HBV, even in a low-incidence country like Germany [14] .…”
Section: Nat-negative Window Period Infections In Blood Donorsmentioning
confidence: 75%
“…He developed typical acute hepatitis B five months later [12] . A second similar case has also been described [13] . The long early window period leads to the relatively large residual risk of 1: 360,000 for undetected HBV, even in a low-incidence country like Germany [14] .…”
Section: Nat-negative Window Period Infections In Blood Donorsmentioning
confidence: 75%
“…In spite of the global HBV vaccination program, hepatitis B is still problematic in blood products. Depending on the point that OBI may be regarded as a crucial risk factor for HBV transmission in blood recipients, several researchers have evaluated the prevalence of OBI in blood donors and have also assessed the hazard of OBI transmission through blood and blood products (14) . It should be mentioned that occult HBV patients may develop HBsAg seroreversion, with subsequent HBV reactivation after chemotherapy, particularly in the cases of serious immunosuppression, such as patients of hematopoietic stemcell transplantation and also, those getting rituximab-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients might experience liver failure and death. Most of these patients are remained in a persistent carrier condition and might cultivate chronic liver disorders, accompanied with its antecedent additional complications (14,18,27) .…”
Section: Discussionmentioning
confidence: 99%
“…2 Occult HBV infection detected by HBV DNA testing has been shown in 0.1-2.4% (median 1%) of HBV surface antigennegative, HBV core antibody-positive blood donors in Western countries such as the United States. 3 HBV transmission by blood components negative for HBV surface antigen has occurred historically, [4][5][6] but is highly unlikely with current manufacturing methods. Risk of transmission of hepatitis B from plasma products appears to be negligible when concurrent HBV surface antibody is present in the blood above a certain level (100-200 mIU/ml), and it has been observed that blood containing detectable HBV surface antibody carries no increased risk of transmitting hepatitis B when compared with blood that lacks this antibody.…”
Section: Discussion On Hepatitis B Core Antibody Testingmentioning
confidence: 99%